Perception of pharmacy students of Universiti Teknologi Mara (UiTM) Puncak Alam towards blended learning - Nadzri, Zaty Syazwani (2015)
This study focuses on exploring perceptions of Universiti Teknologi Mara (UiTM) Puncak Alam pharmacy students regarding the advantages and limitations of a type of integrated learning, called blended learning. This study also determines pharmacy students' perceptions on the options of suggestions to improve the quality of blended learning and identify association between level of students' computer literacy and their perceptions towards blended learning by using Pearson Correlation test. Primary data was utilized for this study which was collected by distributing questionnaires to all pharmacy students of UiTM Puncak Alam from First Year until Fourth Year. The respondents consist of 491 pharmacy students where each of them completed 38 items questionnaire. This study found that regardless of the age and year of study, 88% of the pharmacy students disagree that online learning is a waste of time and there is no association between level of students' computer literacy and their perceptions towards blended learning. The main reason why the students enjoy learning in a blended learning environment is because of it allows them to reduce their total travel time each week and related expenses. However, most of them clearly showed their dissatisfaction on the slow internet connectivity problem which has become a major barrier for them to experience the best blended learning experience. Such perceptions must be taken seriously by the faculty and they have to take actions by finding the best ways to overcome and solve these problems in order to provide a good quality of blended learning environment to the pharmacy students.